Presentation and Outcome of Children with Kawasaki Disease: Experience in A Tertiary Care Hospital in Bangladesh - Zabeen, Fahmida; Hassan, M Quamrul; Nazrin, Tahera; Farheen, Chowdhury; Mohammad Iqbal, Abu Sayeed; Hossain, M Istiaque; Sultana, Sabina; Farooq, Nusrat (Dhaka Shishu (Children) Hospital Journal, 2023)
Background: Kawasaki disease (KD) is an acute difficult-to-diagnose febrile illness in children caused by self limiting vasculitis in medium and small sized arteries. Objetive: This study has been conducted to analyze its presenting symptoms, clinical course, laboratory findings, and therapeutic options in a tertiary hospital in Bangladesh to aid early diagnosis and optimum management. Methods: This is a retrospective study where the medical records of 31 children admitted and diagnosed with Kawasaki Disease (KD) in Evercare Hospital Dhaka between 2009 and 2020, were assessed. Through a structured form, the demographic information, clinical profile, laboratory results, and echocardiographic data were obtained from the hospital records and then entered into a Microsoft Excel sheet. Cleaned and verified data were transferred to SPSS program version 23 and analyzed to obtain descriptive statistics. Results: Out of total 31 patients with KD enrolled, 64.5% of the patients were between six months to five years of age with a median age of three years; 97% had an age below 6 months. Though 68% of patients met all the required criteria for KD, one-third (32%) were diagnosed as incomplete KD with fewer manifestations. Along with high fever in all cases, the most common clinical features were polymorphous rash (90%) and changes in extremities (90%) followed by changes in the lips and oral cavity (77.4%), cervical lymphadenopathy (68%) and conjunctival injection (61%). Common laboratory abnormalities found were anemia (90%), leukocytosis (65%), thrombocytosis especially in the second week (78%), high ESR (100%), and elevated CRP (84%). About 42% of patients had cardiac abnormalities at the onset. Seven children (63.6%) had coronary artery aneurysms (CAA) whereas 18% had coronary dilatations. In subsequent followups, coronary artery changes remained almost the same up to 6-8 weeks. After 3-6 months, 87.5 % of children recovered from cardiac abnormality. Conclusion: A high index of suspicion for KD and an active search for compatible findings in children with unexplained fever can help in early diagnosis. Timely initiation of IVIG treatment is needed to reduce the risk of cardiac complications. Young infants under six months of age need further careful early suspicion and evaluation because of their incomplete presentation and more vulnerability to developing cardiac complications. DS (Child) H J 2022; 38(2): 70-78